Authority Of the National Land Agency in The Implementation Of Mediation On Land Disputes In The City Of Gorontalo - Sri Listiani K. Umar; Mutia Cherawaty Thalib; Nirwan Junus (Estudiante Law Journal, 2019)
This research aims to find out the authority of the National Land Agency in the implementation of mediation on land disputes and the obstacles of the Gorontalo City National Land Agency in the implementation of mediation against land disputes. The research method used is empirical.  The results of the research obtained by the author include the Authority of the National Land Agency whose rights are attached to the Gorontalo City Land Office, is the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 11 of 2016 concerning the Settlement of Land Cases is valid based on applicable laws and regulations. So that the Land Agency must resolve disputes that are complained about by the community without having to go through the judiciary if the parties are willing to be mediated by officers in the Land Office in question. Furthermore, the obstacles of the Gorontalo City Land Agency are still a lack of public awareness and understanding of mediation, the absence of the parties to the dispute, as well as the appointed mediator parties, still, the lack of certified mediator personnel and administrative complaints filed by complainants are incomplete.